How do you find the roots, real and imaginary, of y= -2x^2 - 5x + 6 - (x-5)^2 using the quadratic formula?

1 Answer
Aug 18, 2017

You gotta write it in standard form...

Explanation:

first, multiply out:

y = -2x^2 - 5x + 6 -( x^2- 10x + 25)
= -2x^2 - 5x + 6 - x^2 + 10x - 25

...now, collect the terms

= -3x^2+5x -19

...and now you have your coefficients a, b, and c:

a = -3, b = 5, c = -19

...that you can plug into the quadratic formula:

x = (-b +- sqrt(b^2 - 4ac))/(2a)

...and I'll bet you can take it from here.

GOOD LUCK